2022
DOI: 10.18039/ajesi.892559
|View full text |Cite
|
Sign up to set email alerts
|

Fen Bilgisi Öğretmenlerinin Özel Alan Yeterlikleri Bağlamında Öz Yeterlikleri

Abstract: The changes in the education system in order to train individuals who meet the requirements of the age have revealed the need for determining the competencies that teachers are expected to have. In the studies on teacher competencies, which started in the late 90s, besides determining general competencies, specific field competencies were also determined. Science specific field competencies serve as a guide for science teachers and candidates in achieving their professional development goals. Science teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Er (2020) found that male teachers' self-efficacy perceptions were higher than female teachers. In the study conducted by Candaş and Özmen (2022), it was found that teachers' self-efficacy perceptions did not differ significantly according to gender variable. When the total scores of the self-efficacy scale of English teachers were examined according to professional seniority, a significant difference was found in favour of teachers with 0-5 years of seniority.…”
Section: Conclusion and Discussionmentioning
confidence: 89%
“…Er (2020) found that male teachers' self-efficacy perceptions were higher than female teachers. In the study conducted by Candaş and Özmen (2022), it was found that teachers' self-efficacy perceptions did not differ significantly according to gender variable. When the total scores of the self-efficacy scale of English teachers were examined according to professional seniority, a significant difference was found in favour of teachers with 0-5 years of seniority.…”
Section: Conclusion and Discussionmentioning
confidence: 89%